2012
DOI: 10.1111/j.1600-0765.2011.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Signs of the presence of Th17 cells in chronic periodontal disease

Abstract: The results demonstrated a significant increase in the number of some specific markers of Th17 cells in patients suffering from periodontal disease in comparison with normal control subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 42 publications
(57 reference statements)
3
59
0
Order By: Relevance
“…This suggests that IL-21 may be derived from other cell types such as Th17 cells. Recent studies demonstrated the presence of Th17 cytokine in periodontitis tissues (9,54). However, the ability of this T cell subset in producing IL-21 in periodontitis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that IL-21 may be derived from other cell types such as Th17 cells. Recent studies demonstrated the presence of Th17 cytokine in periodontitis tissues (9,54). However, the ability of this T cell subset in producing IL-21 in periodontitis requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, other Th subsets, including regulatory Th cells and Th17 cells, have been demonstrated in periodontal tissues, of which an inverse relationship between these two cell types could be established (8). Whereas Th17 cells promote periodontal inflammation and tissue destruction (9), T regulatory cells are implicated in guard against periodontitis progression (10).…”
mentioning
confidence: 99%
“…The increase of Th17 cells in chronic periodontal patients and by Porphyromonas gingivalis exposure to peripheral blood mononuclear cells in vitro were also recognized (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The main function of IL-17 is to mediate inflammation by stimulating resident cells to secrete potent proinflammatory cytokines like IL-1, IL-6-IL-8 and prostaglandin E2 (PGE2) that exacerbate the inflammatory reaction and tissue destruction. Several studies demonstrated the presence of Th17 cells in chronic periodontitis lesions [37][38][39]. Cytokines produced and induced by Th17 cells like IL-6, IL-23 and IL-1 beta mRNA levels were reported to be elevated in lesions with periodontitis [37].…”
Section: Th17 Cytokinesmentioning
confidence: 99%